Pengaruh Pendidikan Kewirausahaan dan Self Efficacy terhadap Minat Siswa dalam Berwirausaha (pada Siswa Kelas XII SMK Negeri 2 Singaraja) - Kartikasari, Ni Made Sri Rahayu; Santi, Ni Wayan Ayu (Universitas Pendidikan Ganesha, 2024)
The lack of interest in entrepreneurship hinders Indonesia's economy, especially in addressing the high unemployment rate among the youth due to limited job opportunities. Vocational High School (SMK) education plays a crucial role in fostering students' interest in entrepreneurship from an early age, including at SMK Negeri 2 Singaraja, Bali. This research aims to analyze: 1) the influence of entrepreneurship education on students' interest in entrepreneurship; 2) the influence of self-efficacy on students' interest in entrepreneurship; and 3) the simultaneous influence of entrepreneurship education and self-efficacy on students' interest in entrepreneurship. This causal research uses a quantitative approach with a Likert-scale questionnaire, and data is processed using SPSS 26 for Windows. The population includes 12th-grade students of SMK Negeri 2 Singaraja for the 2023/2024 academic year. The sample size, determined through the Slovin formula, is 209 students, selected using simple random sampling. Data analysis uses descriptive statistical analysis, data quality tests, classical assumption tests, and hypothesis testing. The results show that: 1) Entrepreneurship education has a positive and significant effect on students' interest in entrepreneurship (significance value 0.001 < 0.05); 2) Self-efficacy has a positive and significant effect on students' interest in entrepreneurship (significance value 0.000 < 0.05); and 3) Entrepreneurship education and self-efficacy simultaneously have a significant effect on students' interest in entrepreneurship (significance value 0.000). <0.05).